2018
DOI: 10.1073/pnas.1804835115
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain dehydrogenase/reductase governs steroidal specialized metabolites structural diversity and toxicity in the genus Solanum

Abstract: Thousands of specialized, steroidal metabolites are found in a wide spectrum of plants. These include the steroidal glycoalkaloids (SGAs), produced primarily by most species of the genus , and metabolites belonging to the steroidal saponins class that are widespread throughout the plant kingdom. SGAs play a protective role in plants and have potent activity in mammals, including antinutritional effects in humans. The presence or absence of the double bond at the C-5,6 position (unsaturated and saturated, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 29 publications
1
90
0
Order By: Relevance
“…These nitrogen-containing secondary metabolites are commonly glycosylated, presumably to reduce their autotoxicity, forming steroidal glycoalkaloids (SGAs) [ 107 , 108 ]. Steroidal (glyco)alkaloids are generated from cholesterol [ 108 ] (which in turn is produced from the triterpene (C 30 ) squalene [ 109 ]) via a series of hydroxylation, oxidation, transamination, reduction and/or glycosylation reactions that are catalyzed by various GLYCOALKALOID METABOLISM (GAME) enzymes, of which ten have been characterized in tomato thus far [ 107 , 108 , 110 , 111 ]. In addition, the JA-responsive transcription factor GAME9/JRE4 functions as a master regulator of steroidal (glyco)alkaloid metabolism by controlling, either alone or in association with MYC2, the expression of genes coding for key enzymes in the MVA, cholesterol and SGA biosynthesis pathways [ 112 , 113 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…These nitrogen-containing secondary metabolites are commonly glycosylated, presumably to reduce their autotoxicity, forming steroidal glycoalkaloids (SGAs) [ 107 , 108 ]. Steroidal (glyco)alkaloids are generated from cholesterol [ 108 ] (which in turn is produced from the triterpene (C 30 ) squalene [ 109 ]) via a series of hydroxylation, oxidation, transamination, reduction and/or glycosylation reactions that are catalyzed by various GLYCOALKALOID METABOLISM (GAME) enzymes, of which ten have been characterized in tomato thus far [ 107 , 108 , 110 , 111 ]. In addition, the JA-responsive transcription factor GAME9/JRE4 functions as a master regulator of steroidal (glyco)alkaloid metabolism by controlling, either alone or in association with MYC2, the expression of genes coding for key enzymes in the MVA, cholesterol and SGA biosynthesis pathways [ 112 , 113 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of semipolar compounds was carried out with a UPLC-qTOF-MS instrument (Waters Premier; Waters Chromatography) equipped with a UPLC column connected online to a UV detector and then to the MS detector, as recently described (Sonawane et al, 2018). Separation of metabolites was performed by gradient elution (acetonitrile-water, containing 0.1% [v/v] formic acid) on a 100 3 2.1-mm i.d., 1.7-mm UPLC BEH C18 column (Waters Acquity).…”
Section: Profiling Of Semipolar Compoundsmentioning
confidence: 99%
“…Many studies showed that SDR is mainly involved in the growth and various endogenous and exogenous metabolism of substances (poisons) of the organism. Previous studies found that the gene expression level of SDR is significantly higher in a fenpropathrin resistant strain to T. cinnabarinus, suggesting that the resistant strains of T. cinnabarinus may be related to SDR 49 . In 2010, when studying the pathogenic mechanism of Magnaporthe oryzae, it was found that SDR could not only regulate the pathogenicity of Magnaporthe oryzae, but also regulate the overall defense ability of plants 50,51 .…”
Section: Discussionmentioning
confidence: 93%